Empowering transgender individuals: A thematic analysis of workplace challenges and mental health outcomes - Syeda Mariam Arshad; Sonia Naeem (PJPPRP, 2026)
Transgender communities in our society are always considered as a taboo and people are often seen distancing themselves without making any attempt to understand their issues, especially when they try to become financially independent. This study aims to explore the workplace challenges and the impact of societal behavior on the psychological health of transgender community in Lahore, Pakistan. The study was based on Interpretative Phenomenological Analysis (IPA), for which six transgender individuals were selected through the snowball sampling technique and analyzed using thematic analysis. Semi-structured interviews were conducted to collect in-depth information regarding their experiences. Five major themes were identified after the interviews were transcribed including: societal indifferences, challenges faced during employment, impact on psychological health, self- satisfaction after employment and coping strategies. The results of the study indicated that all the participants encountered absurd societal behavior and faced inequity challenges during employment that resultantly had an adverse effect on their psychological health. Furthermore, the findings suggested various coping strategies that participants used in order to cope with undesirable circumstances and majority of them reported social support and use of optimistic self-talk as the most desirable coping mechanism. Furthermore, the participants pointed out discrimination and inequality they faced during employment. The present study can fill the research gaps with reference to our society and will help the mental health professionals to teach them ways to cope up with the challenges they face, additionally the findings will help to improve the experience of transgender individuals at organizational and societal level.